Role of CMV-serostatus and CX3CR1 on lymphocyte kinetics and left ventricular remodelling in patients with acute myocardial infarction. (25th November 2020) - Spray, L; Park, C; Cormack, S; Mohammad, A; Panahi, P; Boag, S; Bennaceur, K; Richardson, G; Arthur, H; Stellos, K; Spyridopoulos, I
Abstract: Background: Patients with latent cytomegalovirus (CMV) infection have higher rates of adverse cardiovascular outcomes, but the reasons for this remain elusive. CMV-induced changes to T-lymphocyte populations, with a proliferation of CMV-specific, CX3CR1+ effector memory cells, may contribute. Effector T-cells are associated with cardiovascular mortality in CMV positive patients, and ischaemia-reperfusion injury after ST-elevation myocardial infarction (STEMI) and primary percutaneous coronary intervention (pPCI). Purpose: To investigate the effect of CMV status on lymphocyte kinetics and cardiac MRI (cMRI) parameters in 52 STEMI patients receiving pPCI, and examine the prognostic relevance of pre-reperfusion lymphocyte count in a large cohort. Methods: We retrospectively analysed the association between pre-reperfusion lymphocyte count, troponin, and long-term survival in 4874 consecutive STEMI patients. Using flow cytometry, we analysed lymphocyte kinetics in 52 STEMI patients, of known CMV status, during and after pPCI. We assessed the impact of CMV status on infarct size, left-ventricular (LV) function and microvascular obstruction with cMRI in the first week after reperfusion in 101 patients. Repeat cMRI at 12 weeks, to assess LV remodelling, was obtained in 48 patients. Results: Pre-reperfusion lymphopenia is an independent predictor of mortality over 7.5 years (hazard ratio for lowest vs highest quartile: 2.0; 95% CI 1.7–2.4; p<0.001), and is associated with higher admission troponins (p<0.001 for lowest vs second-lowest quartile), suggesting lymphocyte count falls prior to reperfusion in response to myocardial injury. CMV positive patients had more cytotoxic T-cells, strongly expressing the fractalkine receptor, CX3CR1. In CMV positive patients these cells fell dramatically by 90 minutes post-reperfusion, and dropped more sharply in patients with extensive microvascular obstruction on cMRI (p≤0.05 in all effector subsets). CX3CR1 expression was lower at 90 minutes post-reperfusion than at 24 hours (return to physiological expression) in all effector T-cell subsets. All subsets lost a similar proportion of their 24-hour value, but consistently lost a larger proportion in CMV positive patients (−27% in CMV+, −18% in CMV−; p=0.007). CX3CR1 expression falls in the presence of fractalkine, and we hypothesise that membrane-bound fractalkine is induced more strongly in CMV positive patients, as soluble fractalkine levels were similar. At 12 weeks, LV remodeling was worse in CMV positive patients (change in end-diastolic volume: +10.7ml vs −6.1ml; p=0.02). Conclusions: Lymphopenia occurs prior to reperfusion in STEMI, and predicts long-term mortality. Effector T-cells drop substantially after reperfusion only in CMV positive patients, likely mediated by CX3CR1-fractalkine interaction, and this is associated with adverse cMRI findings. Remodeling is worse in CMV positive patients at 12 weeks post-STEMI. Funding Acknowledgement: Type of funding source: Public Institution(s)